Konsekuensi Hukum Wanprestasi (Mutaâ€™khortu Alduyun) VS Perbuatan Melawan Hukum (Almumatholah), Biaya Rill Dan Penyelesaiannya Pada Perbankan Syariah. - Azhar, Azhar; Harahap, Mhd. Yadi (Al-Sharf: Jurnal Ekonomi Islam, 2024)
A binding agreement will produce certain laws that bind performance and default. Default dispute resolution can be resolved in two ways, namely by litigation and non-litigation. Resolving defaults on sharia banking products can be resolved by applying for credit restructuring carried out by the bank with the following conditions: The debtor experiences difficulty in paying the principal or interest on the credit. The debtor has good business prospects and is considered capable of fulfilling its obligations after credit restructuring. In contract law, if the debtor does not carry out his obligations after being summoned, then the debtor has defaulted on all legal consequences. In judicial practice, default cases committed by debtors are generally debtors who do not fulfill their obligations to pay debts/installments to the bank. As a result, the creditor confiscates the collateral and the debtor must pay interest, fees and court costs. In Islamic law regarding the law of Unlawful Actions (PMH), the solution requires responsibility (dhamÃ¢n) or compensation. To find out what compensation solutions are carried out by Sharia Financial Institutions (LKS) when acts against the law occur, the author conducted a study on this matter to enrich knowledge. related to resolving business disputes in sharia economicsAbstract is a brief review of the reasons the research was conducted, discussed or the method chosen, important results, and main conclusions. Ideally abstracts that contain the main problems and / or research objectives, as well as discuss or methods used to solve them, and present important findings, conclusions, and implications of research results.